2018
DOI: 10.1007/s11655-018-2838-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electroacupuncture and Mild-Warm Moxibustion on Brain-Gut Function in Patients with Constipation-Predominant Irritable Bowel Syndrome: A Randomized Controlled Trial

Abstract: Both EA and Mox could signifificantly improve some of the most intrusive symptoms of C-IBS patients, and EA was more effective than Mox. The therapeutic effect of these two therapies might through modulating of the brain-gut axis function. (Registration No. ChiCTRTRC-11001349).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 28 publications
0
57
0
Order By: Relevance
“…As is well-known, visceral hypersensitivity has been deemed as an important neurological evidence underlying the pathogenesis of abdominal pain in IBS, and visceral pain is associated with a dysregulation of the brain-gut axis[ 75 , 76 ]. Some clinical investigations have confirmed the efficacy of acupuncture in the regulation of the abnormal brain activities and improving visceral hypersensitivity in IBS sufferers[ 77 , 78 ]. Moreover, numerous animal studies have also suggested that acupuncture could significantly reduce the peripheral blood flow of rats with 5-hydroxytryptamine positive reactant content and improve visceral hypersensitivity[ 79 - 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…As is well-known, visceral hypersensitivity has been deemed as an important neurological evidence underlying the pathogenesis of abdominal pain in IBS, and visceral pain is associated with a dysregulation of the brain-gut axis[ 75 , 76 ]. Some clinical investigations have confirmed the efficacy of acupuncture in the regulation of the abnormal brain activities and improving visceral hypersensitivity in IBS sufferers[ 77 , 78 ]. Moreover, numerous animal studies have also suggested that acupuncture could significantly reduce the peripheral blood flow of rats with 5-hydroxytryptamine positive reactant content and improve visceral hypersensitivity[ 79 - 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the e cacy of moxibustion in treating IBS-D, but It still remains unclear how moxibustion alleviates IBS-D [29]. Our previous studies indicate that moxibustion could affect intestinal microbes [30,31], visceral hypersensitivity [31,32], the brain-gut axis [14,16], gastrointestinal function [33]. Other studies showed the moxibustion or acupuncture have bene t effect for IBS-D by regulating the neuroendocrine system [34], the immune system [35], and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture and moxibustion are the effective treatment for IBS [12,14], and there are several meta-analyses suggested bene ts of acupuncture and moxibustion in terms of symptom control and quality of life improvements in patients with IBS [13,15]. In our previous studies, we compared the e cacy of electroacupuncture with mild moxibustion for treating IBS-C and IBS-D, respectively, and showed that electroacupuncture resulted in symptoms improvement, modulating on brain-gut function in patients with IBS-C [14] and IBS-D [16]. However, these trials focused on the effect of electroacupuncture VS mild moxibustion on IBS, not mild moxibustion VS placebo Participants Participants were recruited from Shanghai Research Institute of Acupuncture and Meridian between May 2017 and December 2019 through hospital-based Wechat, print advertisements, and posters at the outpatient unit.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of moxibustion analgesia has not been adequately explained thus far. Some studies only support the effect of moxibustion in relieving functional visceral pain but cannot ensure its effect for other forms of pain 36,48,49. Zhu et al found that the analgesic effect that moxibustion produced for functional visceral pain should be associated with the regulation of the prefrontal cortex (PFC) and anterior cingulate cortex (ACC), indicating a central regulation mechanism of moxibustion analgesia 50.…”
Section: Discussionmentioning
confidence: 99%